Analisis Penggunaan Media Pembelajaran terhadap Hasil Belajar Peserta Didik di SDN 2 Campang - Yulita Dwi Lestari; Ridho Agung Juwantara; Ambyah Harjanto (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2025)
This research arose from the challenges of improving basic education standards, where student learning outcomes are the primary focus. This study aims to determine the impact of the use of instructional media on the learning outcomes of third-grade elementary school students. While the use of instructional media is an effective strategy for enhancing the learning process, its impact on student achievement requires further investigation. The research method used was a qualitative approach, emphasizing data collection through observation, interviews, and document analysis. This research was conducted by identifying the instructional media used, observing the learning process utilizing these media, and analyzing their effects on student academic achievement. The results indicate that the use of instructional media effectively improves student understanding and academic achievement. This study provides additional evidence of the importance of implementing instructional media in the context of elementary education. Overall, this study provides in-depth insight into the contribution of instructional media to student learning outcomes and its importance in improving the quality of learning at the elementary level.